2017
DOI: 10.1186/s40550-017-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sulphonamides and tetracyclines antibiotic residue contaminants in rural and peri urban dairy value chains in Kenya

Abstract: Background: Antibiotic residues are drug substances found in food from plants or animals initially exposed to antibiotics. In animal husbandry antibiotics have widely been used for the treatment of animal diseases. These residues have the ability to expose the public to serious health hazards. In Kenya drug residues have not only been related to lack of withdrawal periods but also to intentional addition to extend milk's shelf life. Results: The aim of this study was to investigate the occurrence of 13 veterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
(44 reference statements)
3
27
1
Order By: Relevance
“…Similar results were also reported by Bilandžić et al (2011), Rassouli et al (2014), Prado et al (2015). However, higher amounts of samples with antimicrobial residues were found by Aalipour et al (2015), Layada et al (2016), Orwa et al (2017), Rama et al (2017), Wang et al (2017), Khanal et al (2018).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also reported by Bilandžić et al (2011), Rassouli et al (2014), Prado et al (2015). However, higher amounts of samples with antimicrobial residues were found by Aalipour et al (2015), Layada et al (2016), Orwa et al (2017), Rama et al (2017), Wang et al (2017), Khanal et al (2018).…”
Section: Discussionsupporting
confidence: 89%
“…Recently (2017), in nearby Nakuru County, 28.8% (23/80) of milk samples from peri-urban areas were positive for antibiotic residues. 16 Among our noncommercial samples (MVM + street vendor) in Eldoret, we observed 23.6% (13/55) positive.…”
mentioning
confidence: 69%
“…In addition, with regard to tetracycline, the screening method sensitivity used here was at 50 ppb rather than 100 ppb (Table 1), and positive detections of tetracyclines in Kenyan milk by screening are not always substantiated after analytical laboratory evaluation. 16 It is noteworthy that no commercial samples tested positive using the SNAP screening methods.…”
mentioning
confidence: 99%
“…Antibiotic residues in animal source food are the potential causes of antibiotic resistance in bacteria. Other studies elsewhere have also reported high levels of antimicrobial residues in milk [ 8 , 53 – 55 ]. The differences in antibiotic residue levels in milk may be due to different production and monitoring systems and laboratory analysis used in testing of the antimicrobial residues.…”
Section: Discussionmentioning
confidence: 93%